A study on microstructure and porosity of NiTi alloy implants produced by SHS - Tosun, Gul; Ozler, Latif; Kaya, Mehmet; Orhan, Nuri (Elsevier Science Sa, 2009)
In this study, Ni and Ti with 50.5 at.% Ni powders were blended for 12 h and cold pressed in the different pressures (50, 75 and 100 MPa). Then, the porous NiTi alloy compacts obtained were synthesized by SHS (self-propagating high-temperature synthesis) at the different preheating temperatures (200, 250 and 300 degrees C) and heating rates (30, 60 and 90 degrees C/min). The effects of the pressure, preheating temperature and heating rate were investigated on the porosity and the microstructure. NiTi was seen as the dominant phase in the microstructure with other secondary intermetallic compounds. The porosity of the synthesized products was in the range of 50.7-59.7 vol.%. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: NiTi; SHS; Microstructure; Porosity